2012
DOI: 10.1530/jme-11-0145
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens and atherosclerosis: insights from animal models and cell systems

Abstract: Estrogens not only play a pivotal role in sexual development but are also involved in several physiological processes in various tissues including vasculature. While several epidemiological studies documented an inverse relationship between plasma estrogen levels and the incidence of cardiovascular disease and related it to the inhibition of atherosclerosis, an interventional trial showed an increase in cardiovascular events among postmenopausal women on estrogen treatment. The development of atherosclerotic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
67
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 199 publications
2
67
1
3
Order By: Relevance
“…Previous research has focused on the anti-proliferative and anti-migratory properties of estrogen on VSMCs (29). Here, we elucidated a novel atheroprotective effect of estrogen that E2 promotes cholesterol efflux from VSMCs and suppresses VSMC-derived foam cell formation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous research has focused on the anti-proliferative and anti-migratory properties of estrogen on VSMCs (29). Here, we elucidated a novel atheroprotective effect of estrogen that E2 promotes cholesterol efflux from VSMCs and suppresses VSMC-derived foam cell formation.…”
Section: Discussionmentioning
confidence: 92%
“…Pre-incubation with ICI 182,780 to antagonize ERs blocked the E2-mediated upregulation of LXRα, ABCA1 and ABCG1 expression and attenuation of cholesteryl ester accumulation in VSMCs, indicating ER dependence. There are two different isforms of ERs, ERα and ERβ, which are expressed in endothelial cells, VSMCs and macrophages (29). Previous research found that ERα may be the major mediator of the atheroprotective effects of estrogen (40).…”
Section: Discussionmentioning
confidence: 99%
“…The Tromsø cohort was derived from community-dwelling men with a prevalence of CVD that was slightly higher than our community-dwelling group (17.5% vs 9.6%) [11]. The SHIP cohort was derived from a population characterised by a relatively high prevalence of cardiovascular risk factors, although the proportion of men with tor subtypes and cellular targets [37]. Therefore, further studies are needed to clarify whether E2 differentially modulates cardiovascular risk in men with either early or more advanced degrees of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue hypoxia can trigger the anomalous angiogenesis by vascular cells which are increasing the vascular endothelial growth factor (VEGF) synthesis. It was also shown that the hypoxia decreases the endometrial blood flow and increases the production of oxygen active forms at endothelial dysfunction syndrome [27,28]. This process can also increase the VEGF and angiopoetin-2 (Ang-2) synthesis in endometrial endothelial cells [11,29].…”
Section: Discussionmentioning
confidence: 98%